ILLEGAL ACCESS THROUGH "WIRELESS FIDELITY" IN CRIMINAL LAW - Aida Dewi; Hartanto Hartanto; Arvita Hastarini (Jurnal Meta-Yuridis, 2023)
The internet is a sophisticated tool for exchanging information, various fields from law to medical sciences (medicine) have also used the internet on a large scale. The use of wireless fidelity is also quite attractive for those who need free internet access. But it is undeniable that in addition to some people hoping to use the free internet, it will also cause the desire of people who want to use it as a means of other crimes. The purpose of this study is to examine cases of internet data theft through wireless fidelity within the scope of criminal law. Our criminal law as  the backbone, namely the Criminal Code, was used to study this problem (historical interpretation) and today there is a Telecommunications Law and an Electronic Information and Transaction Law. While using internet access without someone else's permission, is a violation of the law. Before entering into the study of how much loss quota (intangible objects) were stolen, the perpetrators had actually been able to be suspected by illegal access.